Potential antigenic targets used in immunological tests for diagnosis of tegumentary leishmaniasis: A systematic review. - Mariana Lourenço Freire; Felipe Dutra Rêgo; Gláucia Cota; Marcelo Antônio Pascoal-Xavier; Edward Oliveira (PLoS ONE)
Immunological tests may represent valuable tools for the diagnosis of human tegumentary leishmaniasis (TL) due to their simple execution, less invasive nature and potential use as a point-of-care test. Indeed, several antigenic targets have been used with the aim of improving the restricted scenario for TL-diagnosis. We performed a worldwide systematic review to identify antigenic targets that have been evaluated for the main clinical forms of TL, such as cutaneous (CL) and mucosal (ML) leishmaniasis. Included were original studies evaluating the sensitivity and specificity of immunological tests for human-TL, CL and/or ML diagnosis using purified or recombinant proteins, synthetic peptides or polyclonal or monoclonal antibodies to detect Leishmania-specific antibodies or antigens. The review methodology followed PRISMA guidelines and all selected studies were evaluated in accordance with QUADAS-2. Thirty-eight original studies from four databases fulfilled the selection criteria. A total of 79 antigens were evaluated for the detection of antibodies as a diagnostic for TL, CL and/or ML by ELISA. Furthermore, three antibodies were evaluated for the detection of antigen by immunochromatographic test (ICT) and immunohistochemistry (IHC) for CL-diagnosis. Several antigenic targets showed 100% of sensitivity and specificity, suggesting potential use for TL-diagnosis in its different clinical manifestations. However, a high number of proof-of-concept studies reinforce the need for further analysis aimed at verifying true diagnostic accuracy in clinical practice.